Catchwords in British and Bulgarian Media Discourse on Minorities (GRT and Muslims) - Desislava Cheshmedzhieva-Stoycheva (Slavia Meridionalis, 2025)
The paper traces the occurrence of some common phrases related to Gypsies, Roma and Travellers, and Muslims in the media discourses in Bulgaria and the UK. The findings are based on two different sets of corpora: on the one hand, a corpus of all articles on GRT and Muslims published in the British The Independent, The Guardian and The Telegraph and the Bulgarian Dnevnik, Sega and Standart in different time periods; on the other hand, the Bulgarian and British electronic corpora of Sketch engine. Using content analysis and the socio-cognitive approach within critical discourse studies, the analysis focuses on the use of the terms Roma inclusion, Gypsyization, itinerants, mobile children, BAME, and jihad in media discourse and the changes in meaning these words and phrases undergo, and their significance for the people they denote. The study shows that some uses have died out, others have changed or their meaning has narrowed, while still others are just gaining momentum.